Penerapan Sanksi Pidana Menurut Sistem Peradilan Pidana Anak - Badaru, Baharuddin (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2022)
At present, there are many children whose behavior is deviant or has violated the law, as happened a few months ago when several children carried out a narcotics party in a place in Mamuju City. Likewise, some children do wild races on the highway at night so that they can disrupt public order. This fact shows that such behavior is very worrying and is a problem that can unsettle the community and can endanger the country in terms of how the nation's progress and decline are very much determined by how that nation treats and educates its children. With the enactment of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, children must be protected under Law Number 35 of 2014 concerning Child Protection